Effects of AntiMycobacterium Tuberculosis Nanoherbal Legundy Leaf Extract (Vitex trifolia) - Dwiyanti, Atika; Mulyani, Siti; Yulhan, Oche Axena; Lubis, Humairah Medina Liza; Roslina, Ance (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2021)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis. Indonesia ranks 2nd largest in the world after India. Resistance to anti-tuberculosis drugs is one of the difficulties in treating tuberculosis. This research aim to determine the effectiveness of legundi (Vitex trifolia) leaf extract nanoherbal in killing Mycobacterium tuberculosis. This study was conducted with an experimental design using M. tuberculosis colonies taken from 25 samples of aspirate of tuberculosis patients with lymph nodes and then given the ethanol extract of legundi leaves (70% and 90%) with the process of making nanoparticle extracts. The evaluation of the observations was in the form of measuring the inhibition zone for bacterial growth which were categorized as weak ( 5mm), moderate (6-10mm), strong (11-20 mm) and very strong ( 21mm). The results of the study from 6 repetitions found that the inhibition zone category was 0% weak, 39% moderate, strong 52.3%, and very strong 8.7%. Comparison of the concentration of legundi leaf extract to the diameter of the bacterial growth inhibitory zone was analyzed using the Kruskal Wallis test, which found a significant relationship with p value = 0.000 ( 0.05). Legundi's leaf extract can be used as an antibacterial agent for M. tuberculosis.Â